Determination of serine and globulins of alpha, beta and gamma in blood serum, by chemical methods - Morante Miranda, Manuel (1951)
Given the importance that every day is taking in the clinical assessment of disease processes, the results obtained in the laboratory and the radical changes that are being obtained with the new developments, as regards the importance of specific tests for the diagnosis, prognosis and therapy of patients properly, is that the student and the doctor feel an ever greater concern to biochemistry and within it towards obtaining techniques to make significant dosages with accurate and simple methods for application in the everyday use of hospital practice.